The Inequality of Zakat Distribution to the Indonesia’s Impoverished Muslim Urban - Darwis, Muh; Pabbajah, Mustaqim; Harun, Dato' Sudin; Adliyah, Nurul; Fitriani, Fitriani (UIN Sunan Gunung Djati Bandung, 2023)
Zakat, which is supposed to be for the alleviation of poverty, has actually been a source of problems because of the fact that the distribution has not been in line with its objectives. This current study addresses the inequality in the distribution of zakat to impoverished urban. The distribution of zakat is one of the substantial instruments for the Islamic financial ecosystem to alleviate poverty. The distribution of zakat aims to cater to impoverished communities’ needs and provide financial protection. This study relays on a descriptive qualitative research design where data were obtained through interviews and literature study. The data is used to analyse the concept of inequality in relation to poverty as a result of the unequal distribution of zakat. The results of this study indicate that the distribution of zakat is personally and unequally distributed. The unequal distribution of zakat impacts the welfare of people experiencing poverty due to inequality in selecting zakat recipients. Not merely that, zakat, which is relatively small and temporary, cannot support the productive ability of people with low incomes to achieve prosperity. Therefore, it is necessary to assert the prioritized distribution of zakat.